2020
DOI: 10.1016/j.nepr.2019.102654
|View full text |Cite
|
Sign up to set email alerts
|

Educating nurses to deliver optimum care to military veterans and their families

Abstract: The aim of the project was to help prepare the future nursing workforce to provide optimum care for the Armed Forces Community.Structured evidenced-based educational sessions were designed and then delivered at two Universities in England. This educational model included a flipped approach, didactic classroom teaching, blended learning, and information technology.Educational sessions were provided to 468 first year Bachelor of Nursing undergraduate students in 2017 and 2018. A mixed methods evaluation included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This has been enhanced with provision of healthcare to veterans being added to the RCGP curriculum and training of future GPs 15. A bachelor of nursing undergraduate programme has incorporated the care of military veterans and their families into their syllabus so future nurses will have a better understanding of veterans’ healthcare 16. However, there is more education to be done in the UK particularly if comparison is made with the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been enhanced with provision of healthcare to veterans being added to the RCGP curriculum and training of future GPs 15. A bachelor of nursing undergraduate programme has incorporated the care of military veterans and their families into their syllabus so future nurses will have a better understanding of veterans’ healthcare 16. However, there is more education to be done in the UK particularly if comparison is made with the USA.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of devolved nations, this programme could be rolled out across the UK. Ultimately, this initiative seeks to ensure that all GPs (and all those working in primary healthcare) ask their patients: ‘have you ever served in the Armed Forces?’ With the knowledge and training provided as part of the veteran-friendly programme, GPs will be better able to support the health and welfare of veterans (and their families) 16…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-three per cent of respondents reported that the training was useful, 95% that clinicians should be aware of the healthcare needs of the AFC, and 89% indicated that the subject should be included in the undergraduate curriculum (Finnegan et al, 2020).…”
Section: Preparing Nur S E Smentioning
confidence: 99%
“…Although there was some variation in the VCP goals and activities, goals addressed six overlapping areas: (1) increase of information sharing and collaboration among the partner organizations; (2) increase of the VCP's educational efforts about VA and the partner organizations that serve veterans in their communities; (3) increase of access to VA programs and services for community partner organizations; (4) engagement in effective problem-solving related to veterans' needs; (5) working together effectively to accomplish goals and activities; (6) the increase of services to veterans. Each goal represents a dimension of VCP efforts to successfully achieve the ultimate aim-improve Veteran access.…”
Section: Vcp Goals and Practicesmentioning
confidence: 99%
“…Examples abound. In the UK, for example, one initiative by the Armed Forces Veterans (AFV) involves integrating veterans into the national health services (NHS) [3], while other smaller initiatives and community-centered responses focus on improving veterans' healthcare access as well as services to and relations with veterans [4][5][6]. Similarly, studies in Canada clarify the role of community organizations in assisting military families access civilian healthcare [7] and helping homeless veterans access healthcare and improve services for veterans [8].…”
Section: Introductionmentioning
confidence: 99%